Full Excel model: Life-cycle environmental impacts of food & drink products - Poore, J (University of Oxford, 2018)
Full Excel model providing life-cycle impacts of food and drink products. Contains all original inventory data and mid-point impact data, remodelling assumptions, and final standardised results. Requires Microsoft Excel 2007 or later to use.